Expermental Comparison For The Performance of Circular And Square Solar Cell - AI Hamdani, A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An Experimental comparison between the current-voltage characteristic and the efficiency conversion from solar to electric energy were studied for square and circular single crystal silicon solar cell of equal area (35.28 cm2) . The results show that the solar shape is an important factor in calculating the current-voltage characteristics and efficiency of the solar cell. It was shown that the performance efficiency of the square cell is greater by 8.19% than that for the circular cell of equal area. Although the packing factor for the square cells in the solar panel .reached 96% compared with 79% for that for circular cells panel panel, the final cost for the circular cel1s panel is less than square cells panel.